Pemetrexed-carboplatin with intercalated icotinib in the treatment of patient with advanced EGFR wild-type lung adenocarcinoma: A case report. Issue 33 (August 2017) - Xu, Tongpeng; Wu, Hao; Jin, Shidai; Min, Huang; Zhang, Zhihong; Shu, Yongqian; Wen, Wei; Guo, Renhua
Abstract: Rationale: Tyrosine kinase inhibitors (TKIs) are known to have greater efficacy in epidermal growth factor receptor (EGFR) mutation nonsmall cell lung cancer (NSCLC). However, about 10% of EGFR wild-type (wt) patients respond to TKIs. Patient concerns: Several strategies to increase the efficacy of TKIs in wt NSCLC are the subjects of ongoing investigations. One of them is combining EGFR TKI with intercalated chemotherapy. Diagnoses: We describe a patient with EGFR wt NSCLC, who was found with ovarian and lung metastasis, was treated with pemetrexed and intercalated icotinib. Interventions: In this case, we reported the successful long-term maintenance treatment of a patient with EGFR wt NSCLC with pemetrexed and Icotinib. The patient (40-year-old female) was found with ovarian masses and lung masses. Pathological, immunohistochemical, and amplification refractory mutation system (ARMS) assay examinations of ovarian specimen suggested the expression of metastatic lung adenocarcinoma with wt EGFR. After failure treatment with paclitaxel-carboplatin, the patient received 4 cycles of pemetrexed plus platinum with intercalated icotinib and then remained on pemetrexed and icotinib. Outcomes: A partial response was achieved after the treatment. The patient's condition had remained stable on pemetrexed and icotinib for more than 20 months, with no evidence of progression. Lessons: To our knowledge, this is the first report using the long-term maintenance treatment with pemetrexed and intercalated icotinib in EGFR wt patient. The therapeutic strategies warrant further exploration in selected populations of NSCLC.